Investigating of Nanyin’s Performance Art - Yongjie, Zhang; ., Palphol (Journal of Ecohumanism, 2024)
This Article aimed to study(1)Investigate the creative background of Nanyin performing arts,understand the emergence of Nanyin performing arts(2)Explore development of Nanyin performing arts,analyze the team accounts and innovative works(3)Discuss the artistic characteristics of Nanyin performing arts,summarize the auditory and visual characteristics of Nanyin as a performing art.The sample was Quanzhou Nanyin Troupe,XinXin Nanguan Ensemble,Siong Leng Musical Association.They was selected by literature method,Fieldwork method,Observation method and Quantitative analysis the instrument for collecting data was network and field.Analysis data by Descriptive statistics and Content Analysis.The research results were found as follows; 1.Nanyin performing art is the product of the changing times; 2.Nanyin performing arts have the possibility of continuing to develop; 3.Nanyin performing art has its own artistic uniqueness.